Effects of controlling saline water intrusion in an empoldered area of Bangladesh - Mohammad Chhiddikur Rahman; Tofazzal Hossain Miah; M. Harun-Ar Rashid (Revitalizing the Ganges Coastal Zone: Turning Science into Policy and Practices Conference Proceedings, 2015)
The study explores the effects of controlling saline water intrusion into coastal polder areas of Bangladesh. The study was conducted at the Dacope Upazila of Khulna District (Polder 31) using a predesigned and pretested interview schedule involving 200 farmers. Profitability and undiscounted benefit-cost ratio of rice and shrimp were calculated. Saline water has a significant impact on crop production in the study area and the two unions of Pankhali and Tildanga have a contrasting choice of crops and cropping patterns. Considering the impact of saline water on environment and rice producton, the farmers of the Pankhali union decided to control saline water intrusion and follow a rice-cum-golda (freshwater prawn) cropping pattern. By contrast, the farmers of Tildanga practiced a rice-cum-bagda (brackishwater shrimp) pattern. Water salinity differed significantly between the two unions. Average monthly salinities throughout the year in Pankhali and Tildanga Unions were 7.85 and 12.34 with standard deviations of 7.39 and 8.85, respectively. Lands remained fallow in the boro (dry) season. The benefit-cost ratios of golda and bagda culture were 2.12 and 3.60, respectively. Farmers in Pankhali Union were able to compensate for lower benefits from golda farming with higher returns from T. Aman rice (BCR 1.76) and other benefits such as grazing land, drinking water, vegetables cultivation, boro farming, leasing arrangements and the higher price of golda. The people of Pankhali Union were actively controlling saline water inflow to the polder, whereas those of Tildanga Union preferred saline water because of better financial benefits from bagda farming. Poor farmers of Tildanga were thinking differently; they wanted to grow more rice and vegetables to escape from Hurry (a leasing system) and improve access to their land. According to farmers, the salinity of Pankhali Union is gradually declining due to changed water management and cropping practices. Farmers' are interested in cultivating rice in the boro season and introducing salt tolerant rice varieties to improve productivity and food security. Separate water management policies are needed to facilitate increased productivity of farming at the two different areas.
https://hdl.handle.net/10568/66389
Keywords: 330; Salinity; Coastal; Impact assessment; Adaptation; Vulnerability